Phát triển nguồn tin khoa học và công nghệ trong giai đoạn mới: thách thức, cơ hội và giải pháp - Phạm, Văn Hùng (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Introducing development trends of S&T information market in the world, challenges and advantages of developing S&T information resources at domestic libraries and information organizations. Analyzing opportunities to develop S&T information resources in the current period. Introducing models for collaboration and cooperation with other information-library organizations in online resource development and provision and recommending solutions to develop and utilize S&T information resources at information-library organizations in Vietnam.